Eastern Black Walnut (Juglans nigra L.) Originating From Native Range Varies in Their Response to Inoculation With Geosmithia morbida - Sitz, Rachael A.; Luna, Emily K.; Ibarra Caballero, Jorge; Tisserat, Ned A.; Cranshaw, Whitney S.; McKenna, James R.; Stolz, Joshua; Stewart, Jane E. (Frontiers in Forests and Global Change, 2021)
Thousand cankers disease (TCD) is caused by the walnut twig beetle (Pityophthorus juglandis) vectoring the fungal canker pathogen Geosmithia morbida, which can result in severe dieback and eventual death to species of walnut (Juglans spp.) and wingnut (Pterocarya spp.). This disease is most devastating to the highly valued species J. nigra (black walnut). This species is primarily grown and harvested for timber production in the Central Hardwood Region of the United States, which comprises part of its native range. Management options for TCD are limited; therefore, finding resistant genotypes is needed. Initial studies on black walnut susceptibility to G. morbida documented some genetic variation and suggested potential resistance. Furthermore, G. morbida is thought to be native to the United States, which may have allowed for co-evolution. To capture the representative genetic diversity and screen for resistance to G. morbida, J. nigra families were collected from across the native range. These wild trees, in conjunction with seedlings developed in a black walnut timber improvement program, were planted in a common garden in Fort Collins, Colorado and repeatedly inoculated with G. morbida over the course of four years and three growing seasons. Improved seedlings exhibited larger cankered areas than wild J. nigra of the same provenance. Cankers induced by G. morbida in wild germplasm were smaller on J. nigra collected from the western and central portions of the native range compared to those collected from the eastern portion. Although trees from the western and central part of the range still incurred cankers, our findings indicate that variation in genetic resistance to G. morbida is present in black walnut. This study was performed with G. morbida independent of the walnut twig beetle, but our results suggest the limited G. morbida resistance observed in J. nigra will prevent the full compromise of black walnut to TCD. Results from this study should be taken into consideration in future black walnut breeding programs.